2015
DOI: 10.1021/acs.accounts.5b00126
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Didehydro-Diels–Alder Reaction and Its Impact on the Structure–Function Properties of Environmentally Sensitive Fluorophores.

Abstract: Reaction discovery plays a vital role in accessing new chemical entities and materials possessing important function.1 In this Account, we delineate our reaction discovery program regarding the [4 + 2] cycloaddition reaction of styrene-ynes. In particular, we highlight our studies that lead to the realization of the diverging reaction mechanisms of the intramolecular didehydro-Diels-Alder (IMDDA) reaction to afford dihydronaphthalene and naphthalene products. Formation of the former involves an intermolecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 39 publications
(91 reference statements)
0
22
0
1
Order By: Relevance
“…Solvatochromic fluorophores are molecules with a delocalized aromatic π-system capped with an electron-donating group and an electron-withdrawing group. 28,29 They have been extensively utilized in the design of fluorogenic chemical probes for proteins because their quantum yield increases dramatically when they are embedded in hydrophobic protein interiors (Figure 1, bottom box). 3032 Previous studies have demonstrated their general applicability in biological applications, in particular, live cell imaging.…”
mentioning
confidence: 99%
“…Solvatochromic fluorophores are molecules with a delocalized aromatic π-system capped with an electron-donating group and an electron-withdrawing group. 28,29 They have been extensively utilized in the design of fluorogenic chemical probes for proteins because their quantum yield increases dramatically when they are embedded in hydrophobic protein interiors (Figure 1, bottom box). 3032 Previous studies have demonstrated their general applicability in biological applications, in particular, live cell imaging.…”
mentioning
confidence: 99%
“…The use of didehydro‐Diels–Alder reactions for the preparation of environmentally sensitive probes (Figure 6 B) was recently summarized by Brummond and Kocsis 45. Such processes can afford dihydronaphthalene and naphthalene fluorophores resembling the solvatochromic dye Prodan.…”
Section: Cycloaddition Reactions In Fluorescent Probe Developmentmentioning
confidence: 98%
“…Cycloadditionen mit hetero‐ oder carbocyclischen Partnern wurden im Zusammenhang mit der Fluorophorsynthese ebenfalls beschrieben. Die Verwendung von Didehydro‐Diels‐Alder‐Reaktionen zur Herstellung von umgebungsempfindlichen Sonden (Abbildung B) wurde kürzlich von Brummond und Kocsis zusammengefasst . Solche Prozesse können Dihydronaphthalin‐ und Napthalinfluorophore hervorbringen, die dem solvatochromen Farbstoff Prodan ähneln.…”
Section: Cycloadditionen Bei Der Entwicklung Von Fluoreszenzsondenunclassified